CAGE17-1-Leg1 Cruise Report: Water column observation from CTD and water samples west of Prins Karls Forland, Svalbard - Rasmussen, Tine L.; Niemann, Helge; Gründger, Friederike; Jansson, Per; Sert, Muhammed Fatih; Serov, Pavel; Carrier, Vincent (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
From the afternoon of May 15th to the afternoon of May 19th, CAGE-Centre for Arctic Gas Hydrate, Climate and Environment, the Department of Geoscience UiT, the Arctic University of Norway, arranged a scientific cruise to survey offshore Prins Karls Forland, Svalbard to perform CTD measurements and water sampling on R/V “Helmer Hanssen”. The purpose is to study the variations in methane release and its dependence on oceanographic changes. The area has been continuously surveyed for the last three years for methane concentration, and methane consumption by bacteria and other related data. Because of the good weather conditions time allowed survey of the outer part of the shelf west of Prins Karls Forland – the socalled ‘Masox area’. Here three CTD’s were taken and the area surveyed by echosounding (EK60), chirp and multibeam for combined flare survey (EK60) and geological recording of sedimentary environments (chirp and multibeam). A total of 69 CTD (conductivity-temperature-depth) casts were performed with 12 water bottles sampled for each CTD station.The cruise may be known as: CAGE17_1_leg1
Keywords: Prins Karls Forland; EK60 survey; CTD and water sampling